2021
DOI: 10.3389/fcell.2021.622764
|View full text |Cite
|
Sign up to set email alerts
|

Transient Lipid-Protein Structures and Selective Ganglioside Uptake During α-Synuclein-Lipid Co-aggregation

Abstract: α-Synuclein is a membrane-interacting protein involved in Parkinson’s disease. Here we have investigated the co-association of α-synuclein and lipids from ganglioside-containing model membranes. Our study relies on the reported importance of ganglioside lipids, which are found in high amounts in neurons and exosomes, on cell-to-cell prion-like transmission of misfolded α-synuclein. Samples taken along various stages of the aggregation process were imaged using cryogenic transmission electron microscopy, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
5
14
0
Order By: Relevance
“…For example, αSN 130CF amyloid fibrils formed in the presence of 3 mM of DOPC lipids were mostly composed of antiparallel β -strands, while amyloid fibrils generated with 3 mM of Mimic lipids contained both parallel and antiparallel β -strands ( Supplementary Figures S8,S9 ). Along the same lines, previous studies have reported that alterations in either lipid concentrations or liposome compositions can induce morphologically distinct amyloid fibrils ( Kinoshita et al, 2017 ; Gaspar et al, 2021 ). Amyloid fibrils with different structures showed type-specific fluorescence intensity due to different binding sites of ThT on the surfaces of the amyloid fibrils ( Sidhu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 63%
“…For example, αSN 130CF amyloid fibrils formed in the presence of 3 mM of DOPC lipids were mostly composed of antiparallel β -strands, while amyloid fibrils generated with 3 mM of Mimic lipids contained both parallel and antiparallel β -strands ( Supplementary Figures S8,S9 ). Along the same lines, previous studies have reported that alterations in either lipid concentrations or liposome compositions can induce morphologically distinct amyloid fibrils ( Kinoshita et al, 2017 ; Gaspar et al, 2021 ). Amyloid fibrils with different structures showed type-specific fluorescence intensity due to different binding sites of ThT on the surfaces of the amyloid fibrils ( Sidhu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 63%
“…There are also several other reports on the formation of lipid-protein coaggregates. Both in the case of the early stage of aggregation, involving membrane disruption and protein oligomer formation (Fusco et al, 2014;van Maarschalkerweerd et al, 2014;Fusco et al, 2016;Hannestad et al, 2020), and in the case of mature fibrils (van Rooijen et al, 2009;Grey et al, 2011;Gaspar et al, 2021). However, the very nature of co-aggregation is not fully clear in the case of mature fibrils.…”
Section: Frontiers Inmentioning
confidence: 99%
“…In vivo, the fibril formation process occurs in a highly lipid-rich environment, and Lewy bodies are known to contain significant amounts of lipid (Shults, 2006;Stefanis, 2012;Araki et al, 2019;Fanning et al, 2020;Lashuel, 2020). These facts have motivated studies of αS-lipid interactions, involving both monomeric (Fusco et al, 2014;van Maarschalkerweerd et al, 2014;Fusco et al, 2016;Hannestad et al, 2020;Makasewicz et al, 2021), andfibrillar αS (van Rooijen et al, 2009;Hellstrand et al, 2013b;Galvagnion et al, 2019;Gaspar et al, 2021). It has been shown that monomeric αS adsorbs to anionic lipid membranes (Jao et al, 2004;Pfefferkorn et al, 2012;Hellstrand et al, 2013a;Fusco et al, 2014), and that the membrane under some conditions can have a catalytic effect on fibril formation (Galvagnion et al, 2015;Grey et al, 2015;Galvagnion, 2017;Gaspar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration that the main component of Lewy bodies is a β-sheet-rich, fibrillar form of αS ( Shults 2006 ; Araki, Yagi et al, 2019 ; Lashuel 2020 ), has motivated extensive studies of αS fibrils ( Waxman and Giasson 2009 ; Alam, Bousset et al, 2019 ; Guerrero-Ferreira, Kovacik et al, 2020 ). It has also been shown that Lewy bodies contain membrane lipids ( Lashuel 2020 ; Mahul-Mellier, Burtscher et al, 2020 ), which has motivated detailed studies on interaction between αS and lipids ( Pfefferkorn, Jiang et al, 2012 ; Andreasen, Lorenzen et al, 2015 ; Iyer and Claessens 2019 ; Lashuel 2020 ), covering systems where the protein is present in the monomeric state ( Jain, Bhasne et al, 2013 ; Fusco, De Simone et al, 2014 ; Fusco, Pape et al, 2016 ; Hannestad, Rocha et al, 2020 ), during the aggregation ( Jiang, de Messieres et al, 2013 ; Galvagnion, Brown et al, 2016 ; Gaspar, Pallbo et al, 2018 ) as well as in the final amyloid aggregates ( Hellstrand et al, 2013b ; Galvagnion, Topgaard et al, 2019 ; Gaspar, Idini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%